Evaluation of efficacy and mechanisms of action of Cannabis sativa extracts with analgesic, anti-inflammatory and antiemetic properties in an in vivo model (Journal of Medical Science, 2017)
University of Medical Sciences participates in the realization of the project titled: „Development of the technology of producing cannabinoids from low THC hemp for use as preparations supporting treatment in oncological patients” awarded by the National Centre for Research and Development under project number: INNOMED/I/11/NCBR/2014. The duration of the grant is 36 months, and the total value of the grant is 28011845 PLN. The project is run by University of Life Sciences in Poznan. Laboratory of Experimental Pharmacogenetics at the Department of Clinical Pharmacy and Biopharmacy, Poznan University of Medical Sciences (PUMS) is realizing the task number 4 titled “Evaluation of efficacy and mechanisms of action of Cannabis sativa extracts with analgesic, anti-inflammatory and antiemetic properties in an in vivo model.” The aim of this project is the development of cannabinoid extract with reduced psychoactive component (THC), which due to its high content of cannabidiol (CBD) is meant to provide analgesic properties, and at the same time to reduce the risk of addiction and overdose. University of Medical Sciences is evaluating the analgesic, anti-inflammatory and antiemetic properties of the extract of Cannabis sativa in animal models coupled with neuropathic pain. Pharmacodynamic effects of plant extracts will be later assessed taking into account the level of selected genes and proteins expression.